YLS-THERAPY: POTENSI SUPERNATAN YOGURT LBAâST SEBAGAI ANTIKANKER SERVIKS BERBASIS BIOMOLEKULER - Permata Sari, Desie Suci; Ridho, Wildan Mochamad; Lizziyyannida, Lizziyyannida; Sholihah, Zurniatus; Putra Pratama, Satya Hanggara; Rahmani, Erita; Riawan, Wibi (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Cervical cancer is the third most diagnosed cancer and the fourth leading cause of cancer death in females in the world. Zebrafish have been used as experimental animals in human tumors because of similar gene expression (70%) than other experimental animals. Yogurt LBA-ST produces SCFA metabolites (acetate, lactate, and butyrate) that can provide anticarcinogenic effects. There has been a vast growth of related research focusing on proliferation and apoptosis without clear mechanism. However, Important concern need to considered in the development of tumors is protein-coding invasion, migration, and adhesion (IMA) of tumor cells. This study aims at investigating (1) Antiproliferation activities of supernatan yogurt LBA-ST (SY LBA-ST) on zebrafish embryos and HeLa cells, and (2) anti-IMAâs pathway on HeLa cells. The anti-cancer property of SY LBA-ST was evaluated by MTT assay for viability and imunositochemistry of MMP-2, Laminin5-y2, Hsp27, and TGF-Î² for anti-IMA mechanism. The data is collected and analyzed using One-Way ANOVA.This study could be concluded that (1) SY LBA-ST increase mortality rate and decreased the hatching rate in zebrafish embryos, LC50 â 20% (v/v),Â (2) supernatant, pellet, and whole yogurt shows antiproliferation activity on HeLa cells, (3) IC50 SY LBA-ST â 30% (v/v) and the ED = 10% (v/v), and (4) the anti-IMAâs pathway was via decrease MMP-2, Laminin5-y2, Hsp27, and TGF-Î² expression (p<0.05 Â± 0.005).Keywords: Â lactobacillus bulgaricus-acidophilus, streptococcus thermophillus, cancer, HeLa, zebrafish